A design action intervention approach in the cork industry towards sustainable product innovation. (2015) - Mestre, Ana
This article presents the documentation of the methodology and implementation of the 'design cork action intervention approach' - a method developed by the author for sustainable product innovation as a strategic factor within the Portuguese cork industry. The key assumption was that cork is a potential material for sustainable product design, and possesses unexplored economic potential. To explore this assumption, a 'design cork project' based on design interventions was implemented within the Portuguese cork industry from 2006 to 2009, intended 1) to develop new sustainable added-value products and solutions; 2) to test said products in international markets; 3) to promote sustainable cork product innovation amongst stakeholders, i.e., industry, academia, designers, and consumers. The project resulted in 37 final cork design solution prototypes exemplifying how the functional and aesthetic properties of cork can be implemented in sustainable product design, in addition to discussing the market trends for those generated concepts.